Z-Small Monoform Modules - Abbas, Muntaha Khudhair; Hadi, Inaam Mohammed Ali (Iraqi Journal of Science, 2024)
In this paper, a new proper generalization of small monoform modules, namely Z-Small monoform modules is introduced and studied. An R-module C is called Z-small monoform module (ZSM module; for short), if every non-zero partial endomorphism of C has Z-small kernel.